Audio-visual production for the University of the Philippines Mindanao a promotion campaign - Cabaral, Basil Niño Y.
Audio-visual production for the University of the Philippines Mindanao: a promotional campaign or simply, AVP for UPMIN, is a production thesis that is originally tasked to come up with a promotional campaign material that would serve as the university's visual aid for UPCAT Campaign and event like such. More than the video production itself, this thesis is aimed to document and feature the learning, knowledge and skills the researcher acquired in his four years of college. This will serve as a production manuscript or journal, which will be the record of the researcher's experiences, findings, and setbacks. The main theory that the researcher used as guide in doing this thesis is the Visual Literacy theory, where in it is said, that everything a person produces (in this case a video) he envisions in his mind first. The researcher also followed and pursued the guidelines and principles set by Anthony Friedmann in his book Writing for Visual Media. This includes the Seven Steps Method of Conceptualizing for a production and storyboarding, among the many. With the researcher following the said concepts, things became a lot easier and more convenient for him. The researcher being not an expert in video production, he had difficulty going about this production thesis. Although he had some people work with him, it was still rather difficult as compared to, maybe if he was more proficient in the said field. Despite the many minor dilemmas the researcher came across with, he would still say hat he was successful in doing and finishing this production thesis. It took him several months to finish the writing of this paper and even longer, to complete the shooting and editing of the video; but results are all worth the sleepless nights and the haggard of shooting and editing. Producing a video might sound simple and uncomplicated, while this is true to those who have mastered and perfected this art, it is rather the opposite, the beginners and amateurs. Video production is a complicated process that involves a lot of planning, strategizing and thinking , but this could be made simple by a lot of practice and familiarizing.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts